2015
DOI: 10.1111/grs.12095
|View full text |Cite
|
Sign up to set email alerts
|

Morpho‐anatomical traits of root and non‐enzymatic antioxidant system of leaf tissue contribute to waterlogging tolerance in Brachiaria grasses

Abstract: Soil waterlogging is a major abiotic stress that affects the growth and yield of forage grasses in the tropics. Brachiaria forage grasses are widely planted in the tropics to sustain livestock production. An outdoor study was conducted using plastic cylinders under drained and waterlogged soil conditions in order to identify root and shoot traits associated with waterlogging tolerance in Brachiaria ruziziensis (waterlogging sensitive) and Brachiaria humidicola (waterlogging tolerant). For that reason, dry mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Photosynthetic light-response curves describing the photosynthetic capacity, efficiency, and other parameters are commonly used to evaluate photosynthesis performance under environmental stress [ 41 ]. Waterlogging treatments reduced chlorophyll content in some grass species [ 42 , 43 ]. Although high water potential induced stomata closure is considered to be the major reason for reduced photosynthesis during short-term flooding [ 44 ], chlorophyll content reduction may eventually result in reduced photosynthetic capacity during long-term waterlogging stress [ 43 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic light-response curves describing the photosynthetic capacity, efficiency, and other parameters are commonly used to evaluate photosynthesis performance under environmental stress [ 41 ]. Waterlogging treatments reduced chlorophyll content in some grass species [ 42 , 43 ]. Although high water potential induced stomata closure is considered to be the major reason for reduced photosynthesis during short-term flooding [ 44 ], chlorophyll content reduction may eventually result in reduced photosynthetic capacity during long-term waterlogging stress [ 43 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, photosynthesis reduction has also been found when g S does not decline during the early waterlogging periods (Ahmed et al, 2002). Many studies suggested that chlorophyll content reduction may result in reduced photosynthetic capacity during long-term waterlogging stress (Close and Davidson, 2003;Jim enez et al, 2015;Ou et al, 2011), and waterlogging treatment can affect chlorophyll content differently in grass species (Ashraf and Yasmin, 1991;Jiang and Wang, 2006). In our study, the reduced photosynthesis in bermudagrass may be associated with declines in photosynthetic pigments or reduced g S given that both were observed.…”
Section: Methodsmentioning
confidence: 52%
“…S3). On the one hand, anoxic conditions induced by waterlogging impaired photosynthetic e ciency and antioxidant system of plants, suppressing plant growth (Jiménez et al 2015). On the other hand, the nutrient demand was supposed to be high under soil anoxia for maintaining plant biomass (Rubio and Lavado 1999).…”
Section: Discussionmentioning
confidence: 99%